Сравнительное правоведение: Проблемы и суждения - Арустамян, Рита (Լիմուշ հրատ.)
Իրավաբանական մեթոդների շարքում հատուկ ուշադրության է արժանանում իրավահամեմատական մեթոդը:Պետությունների միջև տնտեսական հարաբերությունների զարգացումը արդի փուլում, ինտենսիվ զարգացումը այլ բնագավառներում պահանջում են տարբեր երկրների իրավունքի մերձեցում և միասնականացում: Այստեղից էլ արտասահմանյան իրավական համակարգերի ուսումնասիրման հետաքրքրությունը և իրավահամեմատական մեթոդի ուսումնասիրման անհրաժեշտությունը: Среди методов юридической науки, привлекающих особое внимание ученых – юристов, выделяется сравнительно правовой метод. Развитие экономических отношений между государствами на современном этапе, интенсивное расширение сотрудничества в иных сферах требует сближения и унификации права различных стран. Отсюда интерес к изучению зарубежных правовых систем и необходимость в разработке сравнительно- правового метода. Among the legal methods the special attention of scholars special is given to legal comparative method. The current stage of development of economic relations between states, the intensive development of cooperative ties in other areas requires convergence and unification of the law in various countries. There arouses immense necessity to study foreign legal systems and legal comparative methods. Among the legal methods the special attention of scholars special is given to legal comparative method. The current stage of development of economic relations between states, the intensive development of cooperative ties in other areas requires convergence and unification of the law in various countries. There arouses immense necessity to study foreign legal systems and legal comparative methods.
Keywords: Правоведение; Юриспруденция